Anti ulcer activity of ethanol extract of the stem bark of Careya arborea Roxb. - Kumar, Kamal; Mruthunjaya, Kenganora; Kumar, Satish; Mythreyi, Rajendran (International Current Pharmaceutical Journal, 2013)
The aim of the study was to determine anti ulcer activity of stem bark of Careya arbore Roxb. on the Wister strain albino rats. Dried stem bark of Careya arbore Roxb. was powdered and this coarse powder was extracted with 70% ethanol by soxhlet extraction method to yield a Ethanol extract of stem bark of Careya aborea Roxb. (EECA). The extract was subjected for preliminary phytochemical analysis and was evaluated for anti ulcer activity against various models such as Ethanol induced, cold restraint stress induced and Pylorus ligation induced models. In acute toxicity study, EECA was found to be safe till 3000mg/kg. So the doses of EECA at various concentration of 300 and 600mg/kg body weight was administered orally, twice daily for 5 days for prevention of ulcer from Pylorus ligation, Ethanol and cold restraint stress - induced ulcers. Analytical parameters like Percentage of Ulcer protection was calculated based on Ulcer index and Gastric juice volume, pH and acidity of gastric juice. Preliminary phytochemical analysis of EECA showed the presence of carbohydrates, glycosides, phytosterols, phenolic compounds, tannins and saponins. The EECA has shown significant activity at both 300mg/kg and 600mg/kg dose level in a dose dependent manner. Phytoconstituents like tannins and saponins may be responsible for anti ulcer activity of EECA. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13633 International Current Pharmaceutical Journal, February 2013, 2(3): 78-82